Effectiveness of a copper based molluscicide for controlling Dreissena adults. Issue 4 (12th February 2019) - Lake-Thompson, Ian; Hofmann, Ron
Abstract : Pilot scale experiments were conducted to test the copper-based EarthTec QZ molluscicide for killing adult quagga mussels. Abstract : Pilot scale experiments were conducted to test the copper-based EarthTec QZ molluscicide for killing adult quagga mussels. The work was done in Lake Ontario water with average water temperatures ranging between 6.7–10.4 °C. Trials consisted of eight copper concentrations varying between 30–500 μg L −1 in triplicate under continuous and cyclical flow regimes. A 1 mg L −1 total chlorine trial was used to provide a comparative standard. Complete control was achieved in all test groups ranging within 7 to 28 days for the copper trials, while the chlorination group required 41 days. The efficacy of the copper product was not impacted by continuous versus cyclical flow regime. Results from this study indicate that the copper based product is a viable molluscicide option for adult control with possible advantages over chlorine in cyclical flow regimes and at colder water temperatures.